PENGARUH PENGUNGKAPAN SUSTAINABILITY TERHADAP PROFITABILITAS DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Raisya Fahira; Makhdalena Makhdalena; Mifta Rizka (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of sustainability disclosure on profitability and its impact on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The population of this study is a manufacturing company that has the data needed in this study (sustainability, profitability, and firm value) totaling 110 companies and all of them are studied (census). he method of data collection in this study uses documentation, the type of data in this study is secondary data sourced from www.idx.co.id.The analysis technique of this research uses simple regression analysis. The results of this study indicate that the disclosure of sustainability has effect on profitability, and profitability has a effect on firm value.Key Words: Sustainability,Profitabilitas,Firm Value